Analisis Perlindungan Ketenagakerjaan Bagi Pekerja Perempuan Dan Anak - Dewi, Dewi Naluri Afriyanti; Lodan, Karol Teovani; Dompak, Timbul (Dialektika Publik, 2024)
This protection for workers means ensuring comprehensive protection for workers, including aspects of safety, health, basic rights and fair treatment. In writing this article using library research. Literary studies cannot be separated from scientific literature. Manpower regulates female workers based on Law no. 13 of 2003 article 76 paragraph 4. Then the rights and protection of child workers are also regulated in Labor Law no. 13 of 2003. Then it is also regulated in the Regulation of the Minister of Manpower and Migration of the Republic of Indonesia Kep. 235/MEN/2003 concerning work that endangers health. The results show that worker protection for women and children is not in accordance with regulations. This can be seen from working hours that do not take into account employee health with a morning, afternoon and evening shift system, division of work in several companies which endangers women.